Massive edema of ovary with cytogenetic alteration of chromosome 12q13-15 in adolescent patient: a case report - De Cecio Rossella; Cantile Monica; Fortunato Nicola; De Chiara Annarosaria; Losito Nunzia Simona; Franco Renato; Botti Gerardo (BMC, 2013)
Abstract Background The massive edema of ovary, with or without fibromatosis, is a rare tumor-like entity characterized by an increase in volume of one or both ovaries for accumulation of edema fluid in the stroma that separates the follicular structures. Case We report a rare case, very peculiar also for its association with a massive stromal fibromatosis and for the presence, never described, of tumoral areas with CHOP gene translocation, on chromosome 12q13-15.